Luminescence in Manganese (II)-Doped SrZn2S2O Crystals From Multiple Energy Conversion - Ma, Ronghua; Wang, Chunfeng; Mao, Shaohui; Shao, Yonghong; Wang, Zhihao; Wang, Yu; Peng, Dengfeng (Frontiers in Chemistry, 2020)
Under the excitation of ultraviolet, X-ray, and mechanical stress, intense orange luminescence (Mn2+, 4T1 → 6A1) can be generated in Mn2+-doped SrZn2S2O crystal in orthorhombic space group of Pmn21. Herein, the multiple energy conversion in SrZn2S2O:Mn2+, that is, photoluminescence (PL), X-ray-induced luminescence, and mechanoluminescence, is investigated. Insight in luminescence mechanisms is gained by evaluating the Mn2+ concentration effects. Under the excitation of metal-to-ligand charge-transfer transition, the most intense PL is obtained. X-ray-induced luminescence shows similar features with PL excited by band edge UV absorption due to the same valence band to conduction band transition nature. Benefiting much from trap levels introduced by Mn2+ impurities, the quenching behavior mechanoluminescence is more like the directly excited PL from Mn2+ d-d transitions. Interestingly, this concentration preference leads to varying degrees of spectral redshift in each mode luminescence. Further, SrZn2S2O:Mn2+ exhibits a good linear response to the excitation power, which makes it potential candidates for applications in X-ray radiation detection and mechanical stress sensing.